Anisotropic rearrangement of the substrate atoms during Ar bombardment on Pd(0 0 1) surface - Kim, Sang-Pil; Kim, Byung-Hyun; Kim, Haeri; Lee, Kwang-Ryeol; Chung, Yong-Chae; Seo, Jikeun; Kim, Jae-Sung (ELSEVIER SCIENCE BV, 2011)
Using a three-dimensional molecular dynamics (MD) simulation, we investigated the atomic scale rearrangement that occurs on a Pd(0 0 1) surface after energetic bombardment by Ar at room temperature. High energy Ar bombardment provoked the significant rearrangement of Pd atoms in a ballistic manner with a fourfold symmetric lateral distribution aligned along the < 1 1 0 > direction. The MD simulation of uniform Ar bombardment at normal incidence on a Pd surface reproduced the experimentally observed fourfold symmetric nano-scale surface structure. The present result supports that the ballistic rearrangement of the substrate atoms plays an important role in the ion induced surface structure evolution. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ION-BOMBARDMENT; MOLECULAR-DYNAMICS; PT(111)